Chronic diseases attributable to a diet rich in processed meat in Brazil: Burden and financial impact on the healthcare system - Rocha, Carla Eduarda Faustino; Parajára, Magda do Carmo; Machado, Ísis Eloah; Vegi, Aline Siqueira Fogal; Menezes, Mariana Carvalho de; Meireles, Adriana Lúcia (Frontiers in Nutrition, 2023)
Background The consumption of processed meat causes negative impacts on health; however, this burden for the population living in developing countries is less explored. This study aimed to describe the burden of chronic noncommunicable diseases (NCDs) attributed to a diet rich in processed meat between 1990 and 2019 in Brazil and its federative units and the financial burden on the Unified Health System (SUS) in 2019. Methods Secondary data from the Global Burden of Disease (GBD) and SUS Information Systems were used in this ecological study. The metrics to assess the burden of NCDs attributable to processed meat consumption were disability-adjusted life years (DALYs) and deaths. The age-standardized rates were presented per 100,000 inhabitants with 95% uncertainty intervals (95% UI). The cost of hospitalizations and outpatient procedures covered by SUS for the treatment of NCDs attributable to processed meat consumption was estimated using the population-attributable fraction. Both burdens were estimated for both sex and stratified by sex, specific cause, and federative units. Results The age-standardized DALY rates attributable to a diet rich in processed meat increased between 1990 (75.31/100,000 [95% UI: 34.92–139.65]) and 2019 (79.35/100,000 [95% UI: 42.84–126.25]); while mortality rates remained stable between 1990 (2.64/100,000 [95% UI: 1.17–5.21) and 2019 (2.36/100,000 [95% UI: 1.22–4.09]). The cost of hospitalization and outpatient procedures in Brazil for NCDs attributable to the consumption of processed meat was approximately US 9,4 million, of which US 6,1 million was spent on ischemic heart disease, US 3,1 million on colorectal cancer, and US 200 thousand on type 2 diabetes mellitus. Conclusion The NCD burden did not decrease during the years evaluated, while the financial burden was high in 2019, with higher treatment costs for ischemic heart disease. These results can guide political, economic, and health education interventions to advance the fight against NCDs.